Assessment in special education : a practical approach - Pierangelo, Roger; Giuliani, George A. (Upper Saddle River, New Jersey : Pearson Education, 2012)
Unique in its perspective, the fourth edition of Assessment in Special Education covers assessments for every disability type while examining each stage of the assessment process. Unlike other books, it is organized chronologically and moves sequentially through response to intervention, to prereferral strategies, to assessments, to report writing, to development of the IEP. Chapters discuss the most current and reliable assessment measures used in schools to determine all areas of special need from infancy, to school-age and into adulthood. This edition addresses current topics such as IDEIA, curriculum-based assessment, curriculum-based measurement, functional behavior assessments and behavioral intervention plans. Early chapters are devoted to foundational concepts, while later chapters tackle practical topics such as interpretation, diagnosis, report writing, recommendations, parent involvement and eligibility.
Part 1. Foundational concepts in assessment in special education -- 1.Introduction to assessment -- 2. Methods of assessment and testing considerations -- 3. Basic statistical concepts -- 4. Validity and reliability -- 5. Scoring terminology used in assessment -- Part 2. The special education process -- 6. Response to intervention -- 7. The child study team and prereferral strategies -- 8. The multidisciplinary team and parental participation in the assessment process -- 9. Assessment of academic achievement -- 10. Assessment of intelligence -- 11.Assessment of behavior -- 12. Assessment of perceptual abilities -- 13. Assessment of speech and language -- 14. early childhood assessment -- 15. Other areas of assessment -- 16. Determining whether a disability exists -- 17. Writing a comprehensive report in special education -- 18.Eligibility procedures for special education services -- 19. Development of the IEP.
Includes bibliographical references and index.
Keywords: SPECIAL EDUCATION